The third space professional: cultivating authentic learning experiences through collaborative practice - Kate Murray (Journal of Learning Development in Higher Education)
We are witnessing a rise in collaboration between academics and third space professionals, which has resulted in a curriculum design that is far more focused on cultivating new authentic learning experiences and assessment opportunities for students in higher education. This collective approach to teaching and learning not only provides students with real-world experiences but also facilitates the development of student achievement across the designated learning outcomes as defined by Higher Education Institutions (HEI). In this opinion piece, I share my experience as a liaison librarian who is actively working as a third space professional across the subjects of Law, Sociology, Social Policy, and Criminology. Discussion is considered as a vital way for third space professionals to gain trust and credibility amongst academics, as well as the positive impact the introduction of hybrid working had in strengthening these alliances. Collaborative practice is explored in terms of how this can influence the design of authentic learning experiences and encourage innovative ways of assessing students. Research-connected teaching is viewed as a way for the third space professional to scaffold student learning and to develop an academic skills support offer that is robust and experiential.